Effect of lower extremity joint distraction exercises during warm-up on range of motion, flexibility, and jump performance in female volleyball players - Tas, B.; Ok, E.; Akalp, U.; Bingül, B. M.; Gelen, E. (Pedagogy of Physical Culture and Sports, 2024)
Background and Study Aim. Effective warm-up routines are critical for enhancing athletic performance and reducing injury risk. Joint distraction exercises are hypothesized to improve range of motion (ROM), flexibility, and jump performance, yet their effects are not well-documented in volleyball. This study aims to investigate the impact of joint distraction exercises applied to the lower extremities during warm-ups on ROM, flexibility, and jump performance in female volleyball players.